The Influence of Professional Competence of Aqidah Akhlak Teachers on Discipline of Grade 6 Students at Madrasah Ibtidaiyah: Pengaruh Kompetensi Profesional Guru Aqidah Akhlak Terhadap Kedisiplinan Peserta Didik Kelas 6 di Madrasah Ibtidaiyah - Rahmah, Maretha Lailly; Rindaningsih, Ida (Universitas Muhammadiyah Sidoarjo, 2022)
The problem raised in this study is whether there is a positive influence of teacher professional competence on student discipline in class 6 MI Muhammadiyah 3 Penatarsewu. With this goal, teachers must have professional competence so that they can make the student learning process effective and efficient. Competence is an ability that can affect a person's actions and ways of thinking. The purpose of this study was to analyze and help solve problems regarding the effect of the professional competence of Aqidah Morals teachers on the discipline of 6th grade students at MI Muhammadiyah 3 Penatarsewu. To analyze and help solve problems regarding the effect of the professional competence of Aqidah Morals teachers on the discipline of 6th grade students at MI Muhammadiyah 3 Penatarsewu. The researcher used a quantitative method with a questionnaire/questionnaire that was distributed to all students of class 6 MI Muhammadiyah 3 Penatarsewu, totaling 32 students. However, due to the constraints of some students who could not fill out the questionnaire/questionnaire, in the end the researcher only got 22 samples. There are several stages that researchers must go through in research, namely interviews with homeroom teachers to get real problems, formulating hypotheses, making research instruments, collecting data, analyzing data and drawing conclusions. From the results of this study, there is an influence of the Professional Competence of Aqidah Akhlak Teachers on the Discipline of Class 6 Students at MI Muhammadiyah 3 Penatarsewu. The results of a simple linear regression test show that it can be seen that the calculated F value = 26,569 with a significance level of 0.000 < 0.05 This proves the results of the analysis which states that H0 is rejected and H1 is accepted, because the t-count result is smaller than the t-table value. ie 0.000 > ttable 0.05.